Caracterização do padrão do ciclo vigília-sono, avaliado pela actimetria, em uma amostra da população da cidade de São Paulo - Guzzo, Lia Alves Simões Matuzaki [UNIFESP] (2010)
Introduction: There are few studies evaluating the characteristics of the sleep-wake cycle (SWC) patterns in the general population. The aims of this study was to evaluate the SWC in a sample of the São Paulo city population; to assess the characteristics of SWC according to the chronotype; and to compare the polysomnography (PSG) and actimetry simultaneously recorded. Methods: Volunteers were selected from a population based study (São Paulo Epidemiologic Sleep Study), stratified by gender, age (20-80 years-old) and socioeconomic status. SWC was measured for at least three consecutive days using actimetry (Actwach-64®) and sleep diary. Social-demographic, health and sleep habits and complaints data were gathered from the questionnaires and a full-night PSG was performed. Results: Out of a sample of 1101 volunteers selected to represent the adult population of São Paulo, 359 volunteers wore the actimetry properly and 60% were women. The mean age was 43 ± 14 years and the mean total sleep time (TST) was 365 ± 57 minutes. The most of the participants presented monophasic pattern of sleep (92%), 7% had biphasic pattern and 1% had poliphasic pattern. According to a Two-step Cluster analysis, volunteers were included into three groups: morningness (61%), composed of individuals that had the sleep onset around 10:00 PM and TST was 374 ± 52 minutes; eveningness (32%), composed of individuals that had the sleep onset at 2:00 AM and TST was 349 ± 66 minutes; and the other group (7%), who had no defined sleep onset time and TST was 362 ± 58 minutes. We observed a moderate correlation between PSG and actimetry for TST (r=0.7) (p<0.001), and a weak correlation for sleep efficiency (r=0.4) (p<0.001), sleep latency (r=0.2) (p<0,001) and wake after sleep onset (r=0.3) (p<0.001). Conclusions: Our data suggest that the evaluated population presented mostly monophasic sleep pattern. Based on the selection of the variables (sleep onset time, TST, sleep efficiency and sleep latency) the actimetry was reliable to establish the profile of the population according to chronotype. Although differences between the actimetry and the PSG have been observed, the results support the use of actimetry to evaluate the sleep episodes.